7x+6y=-5

Subtract 7x from both sides of the equation.

6y=-5-7x

Divide each term by 6 and simplify.

Divide each term in 6y=-5-7x by 6.

6y6=-56+-7×6

Cancel the common factor of 6.

Cancel the common factor.

6y6=-56+-7×6

Divide y by 1.

y=-56+-7×6

y=-56+-7×6

Simplify each term.

Move the negative in front of the fraction.

y=-56+-7×6

Move the negative in front of the fraction.

y=-56-7×6

y=-56-7×6

y=-56-7×6

y=-56-7×6

Choose any value for x that is in the domain to plug into the equation.

Remove parentheses.

y=-56-7(0)6

Simplify -56-7(0)6.

Simplify each term.

Cancel the common factor of 0 and 6.

Factor 6 out of 7(0).

y=-56-6(7⋅(0))6

Cancel the common factors.

Factor 6 out of 6.

y=-56-6(7⋅(0))6(1)

Cancel the common factor.

y=-56-6(7⋅(0))6⋅1

Rewrite the expression.

y=-56-7⋅(0)1

Divide 7⋅(0) by 1.

y=-56-(7⋅(0))

y=-56-(7⋅(0))

y=-56-(7⋅(0))

Multiply 7 by 0.

y=-56-0

Multiply -1 by 0.

y=-56+0

y=-56+0

Add -56 and 0.

y=-56

y=-56

Use the x and y values to form the ordered pair.

(0,-56)

(0,-56)

Remove parentheses.

y=-56-7(1)6

Simplify -56-7(1)6.

Multiply 7 by 1.

y=-56-76

Combine the numerators over the common denominator.

y=-5-76

Subtract 7 from -5.

y=-126

Divide -12 by 6.

y=-2

y=-2

Use the x and y values to form the ordered pair.

(1,-2)

(1,-2)

Remove parentheses.

y=-56-7(2)6

Simplify -56-7(2)6.

Cancel the common factor of 2 and 6.

Factor 2 out of 7(2).

y=-56-2⋅76

Cancel the common factors.

Factor 2 out of 6.

y=-56-2⋅72⋅3

Cancel the common factor.

y=-56-2⋅72⋅3

Rewrite the expression.

y=-56-73

y=-56-73

y=-56-73

To write -73 as a fraction with a common denominator, multiply by 22.

y=-56-73⋅22

Write each expression with a common denominator of 6, by multiplying each by an appropriate factor of 1.

Multiply 73 and 22.

y=-56-7⋅23⋅2

Multiply 3 by 2.

y=-56-7⋅26

y=-56-7⋅26

Combine the numerators over the common denominator.

y=-5-7⋅26

Simplify the numerator.

Multiply -7 by 2.

y=-5-146

Subtract 14 from -5.

y=-196

y=-196

Move the negative in front of the fraction.

y=-196

y=-196

Use the x and y values to form the ordered pair.

(2,-196)

(2,-196)

These are three possible solutions to the equation.

(0,-56),(1,-2),(2,-196)

Find Three Ordered Pair Solutions 7x+6y=-5